Perencanaan dan Perancangan Bangunan Rehabilitasi Narkoba Bertema Modern Tropis di Kabupaten Badung: bahasa indonesia - Dimas Rifky Hidayat; Ni Putu Ratih Pradnyaswari Anasta Putri; Anak Agung Gede Raka Gunawarman (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
The increasing cases of drug crime are widespread in the environment with various addicts of various ages, young and old, from children to adults, especially in Bali. According to data from the Bali Province National Narcotics Agency, drug users during the Covid-19 Pandemic season have begun to increase by 8% with a total of 574 drug cases involving 638 suspected drug cases and 534 total drug abuse patients from 2012 to 2022. Through building design This rehabilitation is expected to reduce drug addicts and be able to cure drug addicts so that they return to society and are able to become individuals who are more productive and creative according to their fields. In this design, we review the designs that have potential and overcome the problems that come from this design, of course by approaching the theory of behavioral architecture, constitution, and standardization of drug rehabilitation centers using design methods that are expected to be able to accommodate this rehabilitation building and fulfill any need for rehabilitation. In this design using 4 aspects of nature, five senses, psychological, environment with the design theme of modern tropical. In this study, an analysis of the location, climate was also carried out and considering aspects of the convenience of users of this facility later.